2017
DOI: 10.1080/10255842.2017.1299142
|View full text |Cite
|
Sign up to set email alerts
|

To reduce the maximum stress and the stress shielding effect around a dental implant–bone interface using radial functionally graded biomaterials

Abstract: In a dental implant system, the value of stress and its distribution plays a pivotal role on the strength, durability and life of the implant-bone system. A typical implant consists of a Titanium core and a thin layer of biocompatible material such as the hydroxyapatite. This coating has a wide range of clinical applications in orthopedics and dentistry due to its biocompatibility and bioactivity characteristics. Low bonding strength and sudden variation of mechanical properties between the coating and the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…For materials intended for long-term implants, such as titanium alloys, materials should be designed with good mechanical properties but as close as possible to those of surrounding tissues, mainly bones. Numerous studies have confirmed that too much difference between mechanical properties (mainly Young's modulus) of implant and bone can lead "shielding effect" and consequently bone lose and even loosening of such an implant [80][81][82]. The Young's modulus of cortical human bone is 10-30 GPa [79].…”
Section: Discussionmentioning
confidence: 99%
“…For materials intended for long-term implants, such as titanium alloys, materials should be designed with good mechanical properties but as close as possible to those of surrounding tissues, mainly bones. Numerous studies have confirmed that too much difference between mechanical properties (mainly Young's modulus) of implant and bone can lead "shielding effect" and consequently bone lose and even loosening of such an implant [80][81][82]. The Young's modulus of cortical human bone is 10-30 GPa [79].…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the biomechanical compatibility of biomaterials used in the construction of implants, especially long-term ones, it is important to determine Young's Modulus [26,42,82,83]. The results of earlier works revealed the influence of this factor on the surrounding living tissue, such as bone [84][85][86][87]. The significant difference in Young's Modulus between implants and human bone (especially cortical human bone~20 GPa) can induce bone loosening and reduced bone quality in the implant surrounding and in consequence loosening of the implant in the bone [88,89].…”
Section: Discussionmentioning
confidence: 99%
“…This results in reduced bone density (osteopenia), and cortical bone thickness of the implant‐associated bone . Altering implant design, stiffness, biomaterial coating, and manufacturing can address stress shielding to some extent.…”
Section: Current Challengesmentioning
confidence: 87%